On the distributional Stieltjes transformation - D. Nikolic-Despotovic; A. Takaci (International Journal of Mathematics and Mathematical Sciences)
This paper is concerned with some general theorems on the distributional Stieltjes transformation. Some Abelian theorems are proved.